2018
DOI: 10.1039/c7qm00452d
|View full text |Cite
|
Sign up to set email alerts
|

Metal-free bifunctional carbon electrocatalysts derived from zeolitic imidazolate frameworks for efficient water splitting

Abstract: Cathodic polarization treatment modulates the surface functional group composition of ZIF-8 derived metal-free carbon catalysts, resulting in enhanced OER/HER activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 56 publications
0
34
0
Order By: Relevance
“…8d), and demonstrated high performances for water splitting with a current density of 10 mA cm −2 over 8 h under a potential of 1.82 V and a faraday efficiency (FE) of 98.0-99.1% in 0.1 M KOH electrolyte [187]. N,P,O-tri-doped porous graphite carbon@ oxidized carbon cloth (donated as: PGC/OCC) has also been developed for overall water splitting with a low overpotential of 410 mV, a current density of 10 mA cm −2 , a small Tafel slope of 83 mV dec −1 , and a long-term electrochemical durability [158].…”
Section: Carbon-based Metal-free Oer/her Bifunctional Catalysts For Wmentioning
confidence: 99%
“…8d), and demonstrated high performances for water splitting with a current density of 10 mA cm −2 over 8 h under a potential of 1.82 V and a faraday efficiency (FE) of 98.0-99.1% in 0.1 M KOH electrolyte [187]. N,P,O-tri-doped porous graphite carbon@ oxidized carbon cloth (donated as: PGC/OCC) has also been developed for overall water splitting with a low overpotential of 410 mV, a current density of 10 mA cm −2 , a small Tafel slope of 83 mV dec −1 , and a long-term electrochemical durability [158].…”
Section: Carbon-based Metal-free Oer/her Bifunctional Catalysts For Wmentioning
confidence: 99%
“…The heteroatoms of B, S, N, P, F, and O hold great potential to alter the intrinsic properties of graphene based materials and enable them to adsorb reactant species on their surface without disturbing their electrical conductivities, which shows the availability of foundation for unusual catalytic performances [65][66][67][68]. Furthermore, it has (4) [118] CoO/NC Pyrolysis 1.0 M KOH 1.55 [151] CoP/NC Annealing 1.0 M KOH 1.73 [147] CoP/rGO Annealing/phosphoration 1.0 M KOH 1.56 [138] CoP/rGO Pyrolysis 1.0 M KOH 0.47 [145] Co-BNC Carbonization 1.0 M KOH 1.68 [180] CoP/NPMG Carbonization 1.0 M KOH 1.60 [149] NiP/C Electrodeposition/phosphoration 1.0 M KOH 1.63 [146] VCN@Fe 4 N/FeOOH Annealing 0.1 M KOH 1.60 [153] NiFe-LDH NS@DG Suspension 1.0 M KOH 1.50 [156] been noted that the modification of graphene via high electronegative heteroatom (e.g., N, F, and O) doping can easily modulate the electronic structures by activating the adjacent carbon atoms in the graphene, leading to increase catalytic sites, which ultimately boosts up the electrochemical activities for water splitting [69]. In addition, the co-doping with higher and lower electronegative heteroatoms can also provide a synergistic effect between heteroatoms with a distinctive electronic structure and consequently enhance the activity of heteroatom-doped graphene-based electrocatalysts [70].…”
Section: Heteroatom-doped Graphene-based Electrocatalysts For Water Smentioning
confidence: 99%
“…The edge defects, large surface area, and high N-doping content were attributed to the remarkable electrochemical performances. Subsequently, a N-doped carbon-based electrocatalyst with largest surface area of 1017 m 2 g −1 , was developed by cathodic polarization treatment (CPT) for different time after pyrolysis of different precursors [118]. The N-doped carbon-based electrocatalysts prepared by using CPT for 6 h and 4 h demonstrated impressive HER and OER activities, with the overpotentials of ~ 0.16 and ~ 0.48 V at 10 mA cm −2 , and Tafel slopes of 54.7 and 78.5 mV dec −1 in acidic media, respectively.…”
Section: D Porous Carbon-based Electrocatalysts For Overall Water Spmentioning
confidence: 99%
“…Moreover, investigation of Raman spectra also showed that higher carbonization time inicts higher number of defects and severe structural damage to the graphitic carbon matrix, thereby lowering activity. 155 ZIF-67 because of its large cobalt content is an automatic choice for carbonization. Porous Co-P/NC nanopolyhedrons comprising CoP x nanoparticles embedded in N containing C matrix was prepared by the direct carbonization of ZIF-67, followed by phosphidation.…”
Section: Bifunctional Electrocatalysts From Mof Derived Materialsmentioning
confidence: 99%